THE IMPACT OF DIGITALIZATION ON ACCOUNTING AND REPORTING: BENEFITS, CHALLENGES AND IMPLEMENTATION STRATEGIES - PELEKH, Ulyana; TENYUKH, Zoryana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Given the rapidity of innovation and technological progress and the digitalization of all aspects of public life, as well as the European integration vector of the development of the Ukrainian economic space, the issue of digital optimization of accounting and reporting processes in the activities of an enterprise is of particular relevance. The study aims to analyze the potential impact of modern digitalization strategies on the accounting and reporting processes of an enterprise. The study found that the digital transformation of accounting and reporting activities of enterprises is positioned as an indispensable component of the development strategy of the modern business environment. The author analyzes the feasibility and prospects of applying innovative capabilities of cloud technologies and artificial intelligence in the field of accounting, as well as means of ensuring an appropriate level of security. The main digital trends in the process of digitalization of accounting and reporting are analyzed, reflecting the vector of the overall development of a sustainable financial environment and circular economy. It is determined that modern digital tools create variable prerequisites for simplifying the processes of collecting, accumulating, analyzing financial information and generating reliable reporting. A number of risks related to the implementation of cloud technologies and artificial intelligence in accounting and reporting systems are identified. It is proved that the intensification of the process of introducing digital technologies into the accounting and reporting processes of an enterprise can increase the accuracy and efficiency of management decisions. It is established that the introduction of remote forms of work and the widespread use of information and communication technologies make it necessary to encrypt informative data and the latest protection strategies. There’s no denying that AI will revolutionize employment in this industry. Among the specific prerequisites for the effective digitalization of accounting and reporting processes in a transition economy are the availability of an appropriate resource base and the readiness of process participants to dynamic changes.